Basic Vocabulary between Oenames Subdialect and Kaesmetan Subdialect of Dawan Language: A Comparative Study - Seno, Dominikus; Gunas, Tobias; Faiqiyah, Layliyatul; Sabatani Jangku, Wilhelmus; Jufidah (Humanis, 2025)
The core vocabulary of the Oenames and Kaesmetan subdialects of the Dawan language spoken in East Amfoang, Timor Island, was compared and contrasted in this study. Six native speakers were observed and interviewed using a descriptive qualitative method, using Morris Swadesh's 200-word list of basic vocabulary as a reference. Key word classes, including verbs, nouns, pronouns, adjectives, numerals, adverbs, and function words, were the focus of the analysis. The results demonstrated that both subdialects share a sizable number of lexical items, and the differences between them were also found. The Kaesmetan subdialect prefers open syllables, vowel retention, and syllabic expansion, whereas the Oenames subdialect tends to maintain compact forms with closed syllables and consonant clusters. This study confirmed that Oenames and Kaesmetan are closely related subdialects, enriching the internal diversity of the Dawan Language.